2010
DOI: 10.3171/2009.10.spine09316
|View full text |Cite
|
Sign up to set email alerts
|

Atypical spine involvement of Erdheim-Chester disease in an elderly male

Abstract: Erdheim-Chester disease is a rare form of non-Langerhans histiocytosis presenting in the 5th through 7th decades of life. Osseous manifestations include symmetrical sclerosis of the long bones and, rarely, the spine. Central nervous system disease commonly affects the white matter tracts as well as the orbits, but epidural disease is rare. To the best of the authors' knowledge, simultaneous epidural and skeletal spine disease has not been reported. The MR imaging characteristics of skeletal spine disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
3
7
0
Order By: Relevance
“…On 2002, Oweity et al reported that 30% of ECD cases exhibit osteolytic lesion involvement [13]. In addition, both typical and atypical ECD lesions may present in atypical foci [32,33]. Both the common and uncommon radiological findings of ECD related osseous involvement should be considered in the differential diagnosis alongside other medical conditions - on a case by case basis.…”
Section: Introductionmentioning
confidence: 99%
“…On 2002, Oweity et al reported that 30% of ECD cases exhibit osteolytic lesion involvement [13]. In addition, both typical and atypical ECD lesions may present in atypical foci [32,33]. Both the common and uncommon radiological findings of ECD related osseous involvement should be considered in the differential diagnosis alongside other medical conditions - on a case by case basis.…”
Section: Introductionmentioning
confidence: 99%
“…Less commonly affected areas include the spinal meninges and the bony spinal column. [8][9][10] When patients do have CNS involvement, they are often symptomatic, with diabetes insipidus and ataxia syndromes being the most common presentations. 5 The purpose of this study was to review the findings on conventional imaging of the brain, head and neck, and spine in patients with ECD who presented to our institution and to identify atypical manifestations.…”
mentioning
confidence: 99%
“…The spinal cord lesion is very rare [4,9,10]; it has been observed in only nine patients including our case, and to the best of our knowledge the intramedullary spinal cord lesion presented in this case has not been documented in previous manuscripts. Spinal cord tumours such as astrocytoma, ependymoma, haemangioblastoma, cavernous haemangioma and malignant lymphoma are listed to be differentiated from ECD but considered to be unlikely because the present lesion included less oedema and no cystic component, haemorrhage and flow void.…”
Section: Discussionmentioning
confidence: 62%
“…As time progressed, the patient noticed weakness in the left upper and lower extremities and the paresis gradually worsened. Laboratory studies revealed a slight increase in white blood cells, 10 . MRI delineated multiple lesions at bilateral cranial convexity, falx, cerebellar tent and left orbital fossa.…”
Section: Case Reportmentioning
confidence: 99%